MINAT BERKUNJUNG : CONTENT MARKETING DAN KEARIFAN LOKAL DESA WISATA KAMPUNG ADAT - Fahimah, Mar'atul; Faizah, Avina Auliatul (Creative Research Management Journal, 2024)
This study aims to examine the effect of Content Marketing and Local Wisdom on Visitor Interest in Segunung Traditional Village Tourism Village Wonosalam, Jombang Regency, East Java. Segunung Traditional Village Tourism Village is a rural-based tourist destination rich in Javanese culture and traditions, offering a unique experience for tourists who want to experience local wisdom and natural beauty. This study uses an associative method with a quantitative approach. The population in this study were potential visitors who saw the Instagram content of the Kampung Adat Segunung Wonosalam tourist village. To obtain data in accordance with this study, researchers used a quantitative approach. The sampling technique uses purposive technique. Data collection by questionnaire. The total respondents in this study were 100 respondents. This study uses multiple linear regression analysis techniques. Based on the test results, it is said that Content Marketing and Local Wisdom partially and simultaneously have a positive and significant effect on Visiting Interest. Content Marketing that is informative and accurate, as well as content that displays real conditions related to tourist village destinations, can increase visitor interest. Local Wisdom, such as local skills that seek to preserve the culture and livelihoods of the community, as well as local decision-making processes that involve the community, create a unique attraction that attracts visitors.